2014
DOI: 10.1111/ics.12175
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of bacterial metabolites prodigiosin and violacein and their potential for use in commercial sunscreens

Abstract: The bacterial pigments prodigiosin and violacein exhibited antioxidant and antimicrobial activities and were able to increase the SPF of commercial sunscreens as well as the extracts of the two plant species tested. These pigments have potential as ingredients for a new product range of and, indeed, represent a new paradigm for sunscreens that utilize substances of biological origin. We discussed the biotechnological potential of these bacterial metabolites for use in commercial sunscreens, and the need for st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 82 publications
(96 reference statements)
3
56
0
2
Order By: Relevance
“…Many bacterial metabolites released from bacterial cells, including alcohols, act as antimicrobials and they frequently presents an obstacle to biotechnologists [2,4,14]. Furthermore, the microorganisms used to carry out fermentations are already stressed by other factors including high sugar concentrations and temperature fluctuations [4,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Many bacterial metabolites released from bacterial cells, including alcohols, act as antimicrobials and they frequently presents an obstacle to biotechnologists [2,4,14]. Furthermore, the microorganisms used to carry out fermentations are already stressed by other factors including high sugar concentrations and temperature fluctuations [4,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Glucose and protease peptone found to affect pigment production positively while heavy metals like Cr 3+ and Ni 2+ had negative effect on pigment production. Other recent studies found that the ecophysiology of pigments produced by bacteria can be exploited for biotechnological purposes [40]. The findings of the current study suggest that phylogenetically diverse types of microbes may potentially yield biotechnologically valuable pigments, and further bio-prospecting efforts are needed to determine how much-untapped potential there is in hitherto uncharacterised microbial pigments.…”
Section: Resultsmentioning
confidence: 67%
“…Prodigiosin protected Bt toxin from sunlight and also enhanced its activity against larvae of both the mosquito species. Prodigiosin and violacein showed good UVprotective ability in combination with commercial sunscreens (Suryawanshi et al 2014). Prodigiosin was found to show mosquito larvicidal activity in our previous studies (Patil et al 2011).…”
Section: Natural Product Researchmentioning
confidence: 85%
“…This effect may be due to environmental instability of violacein, or poor attachment of the molecule to bacterial spore or toxin. Compounds such as violacein and prodigiosin, however, are known to perform an array of ecophysiological roles in biological microbial ecosystems, including protection against UV (Suryawanshi et al 2014).…”
Section: Natural Product Researchmentioning
confidence: 99%